KEYWORD AND COLLOCATION ANALYSIS IN PUBLIC POLICY DISCOURSE: A CASE STUDY OF PRESIDENT PRABOWO SUBIANTO’S SPEECH AT THE WORLD ECONOMIC FORUM 2026 - Mirsa Umiyati (Universitas Nias Raya, 2025)
This research analyzes keywords and collocation patterns in public policy discourse through a case study of President Prabowo Subianto's speech at the World Economic Forum (WEF) 2026. Using a corpus linguistics approach, this study identifies prominent keywords and collocation patterns that form the ideological construction of Indonesian government policies. The research data consists of the president's speech transcript delivered in Davos, Switzerland on January 22, 2026. Analysis was conducted through word frequency identification, keyness calculation, and collocation pattern analysis using a qualitative-quantitative approach. The research findings indicate that dominant keywords include